Registration of 'Bolles' Hard Red Spring Wheat with High Grain Protein Concentration and Superior Baking Quality. Issue 2 (22nd March 2018) - Anderson, J. A.; Wiersma, J. J.; Linkert, G. L.; Reynolds, S. K.; Kolmer, J. A.; Jin, Y.; Rouse, M.; Dill-Macky, R.; Smith, M. J.; Hareland, G. A.; Ohm, J.-B.
Abstract : The hard red spring wheat ( Triticum aestivum L.) market class in the United States commands the highest prices on the worldwide wheat markets because of its high protein concentration, strong gluten, and good baking properties. 'Bolles' (Reg. No. CV‐1140, PI 678430) hard red spring wheat was released by the University of Minnesota Agricultural Experiment Station in 2015 and combines very high grain protein concentration, strong gluten, and good baking characteristics, along with competitive grain yields and good resistance to the diseases Fusarium head blight, leaf rust, stripe rust, and stem rust. Bolles is a mid‐late maturity, semidwarf cultivar that should improve the overall end‐use quality of the hard red spring wheat crop in its region of adaptation in the north‐central United States.